Land use and water quality in watersheds in the state of São Paulo, based on GIS and SWAT data - Veiga, Denise Piccirillo Barbosa Da; Guandique, Manuel Enrique Gamero [UNESP]; Nardocci, Adelaide Cassia (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2019)
Land use influences the quality and availability of water resources, but Brazil has made little progress in integrated watershed management. This study therefore applied geoprocessing for land-use classification and evaluated the impact on the hydrological balance in order to contribute to the integrated management of water resources. Using GIS tools, two drainage areas from the water catchment points of two municipalities, Santa Cruz das Palmeiras and Piedade, were delimited; land-use mapping was carried out using the supervised classification method of satellite images, and the SWAT model was applied for hydrological simulation. The methods used were appropriate. The surface runoff was related to the absence of vegetation and the predominance of exposed soil. The relationship between land use/land cover and the hydrological balance was evidenced, especially the impact of agricultural activities and the lack of natural vegetation in the surface runoff.
Uso do solo e qualidade da água em bacias hidrográficas do estado de São Paulo, utilizando GIS e SWAT
Keywords: Land use/land cover; SWAT; Watersheds management